The Ukrainian economy offshoring: estimation of factors’ impact and developing measures to combat - Hobela, Volodymyr; Podra, Olha; Batyuk, Bogdan; Levkiv, Halyna; Hynda, Oksana (Business: Theory and Practice, 2022)
The study is devoted to the Ukrainian capital outflow analysis, finding main reasons, consequences and working out the recommendations. The purpose of the study was to research the reasons of offshoring, except tax avoidance, to estimate their impact on the state economy and develop the ways of economy de-offshoring based on the main results of the study. The main reasons, positive, negative effects and threats of economy offshoring were identified. The main reasons for offshoring other than tax avoidance were highlighted. Based on empirical, theoretical, and static research, it was found that a corporate raiding, an imperfect legal environment regarding the protection of property, intellectual property and high level of political risks have a significant impact on the economy offshoring. The influence of various factors (x1, x2….xn) on capital outflow was estimated on a base of correlation analysis. According to the received results the main ways of Ukraine’s economy de-offshoring within the formation of institutional and legal support of de-offshoring were developed. Scientific methods such as general and special methods of cognition, methods of economic and statistical analysis, deduction, and the method of theoretical generalization were used in the study.